The usefulness of GGE biplot methodology for line × tester data of maize inbred lines - Momeni,Hossein (2020)
ABSTRACT The genotype + genotype × environment (GGE) biplot methodology has the potential to determine combining ability effects, identify efficient testers, and distinct heterotic groups in a line × tester study. However, it has not been adequately applied for such analysis. Therefore, this study was done to assess the combining ability of some maize inbred lines and testers for grain yield, identify most efficient testers and classify inbred lines into heterotic groups using GGE biplot. Fifteen experimental single cross hybrids, generated from a 5 x 3 line by line × tester crosses procedure, were evaluated across seven sites in Iran in 2018 using a randomized complete block design with three replicates per entry at each site. According to the pooled analysis of variance, crosses showed significant differences for grain yield. Also, the differences observed among the testers, inbred lines, and interactions for the line × tester, crosses × environments, line x tester x environment was significant. The inbred line L4 was recognized as outstanding for its general combining ability (GCA) effect and the tester K18 was highly efficient based on its discriminating power. It can be concluded that the crosses of L4 x K47/3 and L4 x B73 are suggested to release high grain yield hybrids. Results of the GGE biplot analyses were close to the conventional line × tester method in combining ability and heterotic patterns of the yield of lines, grouping, and identification of testers.